Primary cutaneous B-cell lymphomas: Case report of two cases - Shashank Mishra; Divya Shelly; K V Vinu Balraam; Reena Bharadwaj (Wolters Kluwer Medknow Publications, 2017)
Primary cutaneous lymphomas are a unique, heterogeneous group of lymphoproliferative disorders which have a primary cutaneous manifestation in the absence of systemic involvement of lymph nodes, bone marrow, or visceral organs at the time of diagnosis. Among the primary cutaneous lymphomas, B-cell lymphoma is much less common and accounts for 20%-25% of cases. Primary cutaneous diffuse large B-cell lymphomas (PCDLBCLs) are aggressive neoplasms with poor prognosis. Early and accurate diagnosis is required as these patients respond well to systemic anthracycline-based chemotherapy (R-CHOP). In this article, we report two cases of PCDLBCL, other which presented with rapidly enlarging skin nodules and were diagnosed based on clinical features, histomorphology, and characteristic immunohistochemical expression. Both the patients were treated with systemic chemotherapy and responded well. During the 6 months' follow-up period, the lesions regressed. The patients are symptom free with no evidence of disease relapse or dissemination to extracutaneous sites.